Fighting maritime piracy: Three lessons from Pompeius Magnus - Christian Schubert; Leonhard K. Lades (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
Piracy in international waters is on the rise again, in particular off the coast of Somalia. While the dynamic game between pirates, ship-owners, insurance firms and the military seems to have reached some kind of equilibrium, piracy risks generating significant negative externalities to third parties (e.g. in terms of environmental hazards and terrorism), justifying attempts to contain it. We argue that these attempts may benefit from a look back - through the analytical lens of public choice theory - to the most successful counter-piracy campaign ever undertaken, namely, the one led by the Roman general Gnaeus Pompeius Magnus (Pompey the Great) in 67 BC.
Keywords: O17; K42; N43; 330; Piracy; Somalia; Public Choice Theory; Seeräuber; Kriminalpolitik; Public Choice; Somalia; Geschichte; Römisches Reich